Consumer Perceptions of Dynamic Pricing in the Electronics Industry: A Case in Makassar City - Hery Maulana Arif (Malaqbi Publisher, 2026)
Dynamic pricing has proliferated across global electronics retail, yet consumer responses to this practice remain critically underexplored in emerging economies. This qualitative study examines consumer perceptions of dynamic pricing in Makassar City's electronics retail sector, conducted through 27 in-depth interviews and 7 focus group discussions involving 76 participants, and analyzed using reflexive thematic analysis. Five interconnected themes emerged: (1) fragmented awareness—consumers recognize price fluctuations but misattribute them to external economic forces rather than deliberate retailer strategies; (2) conditional fairness—cost-justified variations are acceptable, whereas opaque algorithmic personalization triggers strong unfairness judgments; (3) emotional ambivalence oscillating between excitement at price decreases and betrayal at unexpected increases; (4) strategic decision paralysis manifesting as purchase postponement and compulsive price monitoring; and (5) systematic trust erosion transforming loyal customers into price-sensitive switchers and generating retaliatory negative word-of-mouth. The study introduces the